Provider-level rates of HEDIS-consistent HPV vaccination in a regional health plan - Catherine A. Panozzo; Melissa B. Gilkey; Melanie L. Kornides; J. Frank Wharam (Taylor & Francis Group, 2019)
Background. Health insurers are well-positioned to address low HPV vaccination coverage in the US through initiatives such as provider assessment and feedback. However, little is known about the feasibility of using administrative claims data to assess provider performance on vaccine delivery. Methods. We used administrative claims data from a regional health plan to estimate provider performance on the 2013-2015 Healthcare Effectiveness Data and Information Set (HEDIS) measure for HPV vaccine. This measure required that a girl receive three doses of HPV vaccine by age 13. Providers who administered ≥1 dose in a HEDIS-consistent series received credit for meeting the goal. Results. From January 2008-April 2015, 1,975 (8.5%) of 11-12 year-old girls in our sample received a HEDIS-consistent HPV vaccine series. Our sample of providers consisted of 1,236 who had ≥10 well-visits with different female patients, and 94% of these were pediatricians. A substantial minority of providers (39.4%) did not administer any HEDIS-consistent HPV vaccine doses. Only 5.5% of providers administered HPV vaccine doses that were part of a HEDIS-consistent series to at least one-quarter of their patients. These estimates did not vary by provider sex or age. Doses in a HEDIS-consistent vaccine series were often attributed to multiple providers. Conclusions. In a regional health plan, only 5.5% of providers in our sample administered doses that were part of a complete, three-dose HPV vaccine series to at least one-quarter of their 11-12 year-old female patients.